Identification of Genes Associated with Papillary Thyroid Carcinoma (PTC) for Diagnosis by Integrated Analysis - Li, W.-B.; Zhou, J.; Xu, L.; Su, X.-L.; Liu, Q.; Pang, H. (Hormone and Metabolic Research, 2016)
Papillary thyroid carcinoma (PTC) is the most common type of thyroid carcinoma, and our understanding of its pathogenesis is incomplete. To elucidate the mechanisms underlying such progression and identify novel diagnostic markers, we aimed to discover the underlying gene associated with PTC. Integrated analysis of microarray datasets was performed to identify differentially expressed genes (DEGs) between PTCs and normal tissues. GO enrichment analysis and KEGG pathway enrichment analysis were then performed to uncover the functions of DEGs. Furthermore, the protein-protein interaction (PPI) network of DEGs was constructed. Five GEO datasets were obtained. Totally, 154 DEGs across the studies were identified, including 26 upregulated and 128 downregulated DEGs. In the PPI network, MLLT1, DLG2, and EFEMP1 were the hub proteins, in which DLG2 and EFEMP1 were involved in tumor progression. Among the top 10 up- and downregulated genes, the dysregulation genes of TPO, CDH16, and MPPED2 may be closely related to the tumorigenesis of PTC. By integrated analysis of multiple gene expression profiles, we propose that the dysregulation genes of TPO and MPPED2 will be the promising diagnostic markers for PTCs.
Keywords: papillary thyroid carcinoma; integrated analysis; differentially expressed genes